Potential for selection among nearly neutral allozymes of 6-phosphogluconate dehydrogenase in Escherichia coli. - Hartl, D L (1981)
Six gnd alleles coding for naturally occurring allozymes of 6-phosphogluconate dehydrogenase [6-phospho-D-gluconate:NAD(P)+ 2-oxidoreductase, EC 1.1.1.43] have been transferred by transduction into the genetic background of Escherichia coli K-12 and examined for their selective effects in chemostats in which gluconate was limiting. Four of the alleles are evidently neutral or nearly neutral, inasmuch as their selective effects, if any, fall below the limit of resolution of the procedure--0.5%/hr or about 1% per generation. One allele is detrimental in limiting gluconate but not in limiting glucose or fructose. Another allele has a detrimental, density-dependent, epistatic interaction with tonA. We suggest that all six alleles are neutral or nearly neutral in natural populations but that they are not functionally equivalent; their functional differences are potentially important because they can become expressed as differences in fitness under the appropriate conditions of environment or genetic background. Under these conditions, otherwise neutral alleles can become subject to selection.